Development and testing of the KnowGene scale to assess general cancer genetic knowledge related to multigene panel testing. Issue 8 (August 2019) - Underhill-Blazey, Meghan; Stopfer, Jill; Chittenden, Anu; Nayak, Manan M.; Lansang, Kristina; Lederman, Ruth; Garber, Judy; Gundersen, Daniel A.
Highlights: Patient knowledge contributes to genetic testing decision making. No measure of knowledge exists within the context of multigene panel testing. Knowgene was rigorously developed to meet the need for accurate measures. Knowgene is acceptable for use in patients undergoing multigene panel testing. Abstract: Purpose: To develop and evaluate a measure of cancer genetics knowledge relevant to multigene panel testing. Methods: The instrument was developed using systematic input from a national panel of genetics experts, acceptability evaluation by patient advocates, and cognitive testing. Twenty-four candidate items were completed by 591 breast or gynecological patients who had undergone genetic counseling and multigene panel testing in the past 18 months. A unidimensional item response theory model was fit with a mix of 2-parameter logistic nested response (2 plnrm) and 2-parameter logistic (2 pl) items. Results: Key domains addressing cancer genetics knowledge were found to be overlapping. Of the 24 candidate items, 8 items were removed due to poor discrimination or local dependence. The remaining 16 items had good fit (RMSEA = 0.045, CFI = 0.946) and discrimination parameters ranging from 0.49 to 1.60. The items specified as 2 plnrm distinguish between those answering incorrect versus don't know, with discrimination ranging from 0.51 to 1.02. Information curves were highest among those with lower knowledge. Conclusion: KnowGene is a rigorously developed and effective measure of knowledge after cancer genetic counseling and multigene panel testing. Practice Implications: Measuring knowledge in a systematic way will inform practice and research initiatives in cancer genetics.